RESEPSI KASIDAH BURDAH AL-BÛSHÎRY DALAM MASYARAKAT PESANTREN - Fadlil Munawwar Manshur (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2006)
Qashîdah Burdah is a religious literary work that got an honor reception from the people around the world. Therefore, it is no wonder that Qashîdah Burdah could attract wide interest from the world community in the form of scientific study; Qashîdah Burdah recital in the religious ceremony; consumer’s reception in the recording industry and art performance, comments and translation from the Arabic into various kinds of the world languages: English, French, Spanish, Italian, Dutch, and German. The Nordic languages cover of Norway, Sweden, Denmark, Iceland, and Finland. The next is Russian, Turk, Persian, Urdu, Swahili, Chinese, Indonesian and other languages in Nusantara, i.e., Sundanese, Javanese, and Acehnese.